In vivo evidence of oxidative stress in brains of patients with progressive multiple sclerosis. (July 2018) - Choi, In-Young; Lee, Phil; Adany, Peter; Hughes, Abbey J; Belliston, Scott; Denney, Douglas R; Lynch, Sharon G
Background: The oxidative stress hypothesis links neurodegeneration in the later, progressive stages of multiple sclerosis (MS) to the loss of a major brain antioxidant, glutathione (GSH). Objective: We measured GSH concentrations among major MS subtypes and examined the relationships with other indices of disease status including physical disability and magnetic resonance imaging (MRI) measures. Methods: GSH mapping was performed on the fronto-parietal region of patients with relapsing-remitting multiple sclerosis (RRMS, n = 21), primary progressive multiple sclerosis (PPMS, n = 20), secondary progressive multiple sclerosis (SPMS, n = 20), and controls ( n = 28) using GSH chemical shift imaging. Between-group comparisons were performed on all variables (GSH, T2-lesion, atrophy, Expanded Disability Status Scale (EDSS)). Results: Patients with MS had substantially lower GSH concentrations than controls, and GSH was lower in progressive MS (PPMS and SPMS) compared with RRMS. GSH concentrations were not significantly different between PPMS and SPMS, or between RRMS and controls. Brain atrophy was significant in both RRMS and progressive MS compared with controls. Conclusion: Markedly lower GSH in progressive MS than RRMS indicates more prominent involvement of oxidative stress in the progressive stage of MS than the inflammatory stage. The association between GSH and brain atrophy suggests the important role of oxidative stress contributing to neurodegeneration in progressive MS, as suggested in other neurodegenerative diseases.